2023
DOI: 10.1002/anie.202218493
|View full text |Cite
|
Sign up to set email alerts
|

Scalable Synthesis of Multi‐Metal Electrocatalyst Powders and Electrodes and their Application for Oxygen Evolution and Water Splitting

Abstract: Multi-metal electrocatalysts provide nearly unlimited catalytic possibilities arising from synergistic element interactions. We propose a polymer/metal precursor spraying technique that can easily be adapted to produce a large variety of compositional different multi-metal catalyst materials. To demonstrate this, 11 catalysts were synthesized, characterized, and investigated for the oxygen evolution reaction (OER). Further investigation of the most active OER catalyst, namely CoNiFeMoCr, revealed a polycrystal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
35
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(37 citation statements)
references
References 85 publications
0
35
0
2
Order By: Relevance
“…Moreover, Cechanaviciute et al developed a spraying technique which could apply a precursor solution containing five transition metals onto a three-dimensional nickel foam (Nf) substrate. 102 Among them, the CoNiFeMoCr/Nf material demonstrated a uniform component distribution on the substrate surface and visible disruptions of the lattice on its microstructure. Through operando electrochemistry/Raman measurements of CoNiFeMoCr/Nf, the in situ formation of g-NiOOH active phase during the OER was confirmed (Fig.…”
Section: Nife-based Oer Electrodesmentioning
confidence: 99%
“…Moreover, Cechanaviciute et al developed a spraying technique which could apply a precursor solution containing five transition metals onto a three-dimensional nickel foam (Nf) substrate. 102 Among them, the CoNiFeMoCr/Nf material demonstrated a uniform component distribution on the substrate surface and visible disruptions of the lattice on its microstructure. Through operando electrochemistry/Raman measurements of CoNiFeMoCr/Nf, the in situ formation of g-NiOOH active phase during the OER was confirmed (Fig.…”
Section: Nife-based Oer Electrodesmentioning
confidence: 99%
“…Although multicomponent OER electrocatalysts are of great interest due to their promising electrochemical properties, it is still a challenge to find out the best-performing materials because of a huge number of candidates. Furthermore, affordable OER electrocatalysts having high activity at near-neutral pH conditions are also missing.…”
Section: Introductionmentioning
confidence: 99%
“…The global energy crisis due to the extensive use of fossil fuels has already become a ubiquitous problem, making the domain of renewable energy conversion a hot research topic for the global scientific community. In this regard, electrochemical transformation via electrocatalysis has become an area of research focus because of its potential to convert abundant feedstocks into value-added products. This has in turn led to the design and development of various metal-based and molecular electrocatalysts. Molecular electrocatalysts such as phthalocyanines and porphyrins have gained a lot of attention mainly because of their superior chemical and thermal stability and highly flexible optoelectronic nature. For these reasons, the metallophthalocyanines have been explored for catalysis, like the MEROX process for the sweetening of oils to electrocatalysis in fuel cells and air batteries, with undeniable importance in electrochromism, the pigment industry, sensing, solar cells, and photodynamic therapy (cancer treatment). It is already known that the electrochemical performance of the phthalocyanines can be affected by the redox properties of the central metal which in turn can be altered by changing the metal center or by altering the type, number, and position of the substituents on the macrocyclic ligand. It has also been observed that electron-withdrawing functionalities such as −NO 2 , −CN, −COOH, and −Cl favor oxidation reactions like water electrolysis, oxidation of thiols, ascorbic acid oxidation, peroxide oxidation, etc. On the other hand, electron-donating substituents like t -Bu, −NH 2 , and −OH favor reductive electrocatalysis such as carbon dioxide reduction, oxygen reduction, nitrogen reduction, etc. Therefore, a correlation between electrocatalytic capability and inductive effect of the ligand functionality has already arrived, which is widely chosen as a benchmark for designing new molecular platforms for electrochemical transformations.…”
mentioning
confidence: 99%